Effects of chemotherapy prescription clinical decision-support systems on the chemotherapy process: A systematic review. (February 2019) - Rahimi, Rezvan; Moghaddasi, Hamid; Rafsanjani, Khadijeh Arjmandi; Bahoush, Gholamreza; Kazemi, Alireza
Abstract: Objective: To carry out a systematic review of studies assessing the effects of chemotherapy prescription clinical decision-support systems (CDSSs) on the chemotherapy process. Methods: Articles published in English before May 1, 2017 and indexed in the PubMed and Embase databases were reviewed systematically. Studies that focused on the effects of chemotherapy prescription CDSSs on the chemotherapy process were included in this research and reviewed. Results: 2283 articles were retrieved, of which 37 met the inclusion criteria. Twenty-seven of the included studies reported the effect of chemotherapy prescription CDSSs on medication errors, 18 studies focused on user satisfaction and system acceptance, 10 articles studied the effect of CDSSs on costs and care time and only 3 studies examined the impact on compliance with chemotherapy protocols. Discussion and conclusion: In most of the studies, the use of CDSSs in chemotherapy prescription has reduced medication errors, especially dosage errors and has also reduced the time of chemotherapy process takes. However, in a few studies, the system has not been effective in reducing medication errors, has increased certain type of errors or has introduced new errors. Most of the software used has been specifically designed for the chemotherapy process and is intended to increase user satisfaction and system acceptance. There was not sufficient evidence on the effects of these systems on compliance with protocols and chemotherapy costs to draw firm conclusion. Higher quality studies are required to provide more evidence on the effects of CDSSs on medication errors, user satisfaction and system acceptance, costs, care time and compliance with protocols.